Change Management of Shared and Local Versions of Health-Care Terminologies - Oliver, D. E.; Shahar, Y. (Methods of Information in Medicine, 2000)
Local sites that adopt a shared health-care terminology for computer-based systems have local needs that prompt the local-terminology maintainers to make changes to the local version of the shared terminology. If the local site is motivated to conform to the shared terminology, then the burden lies with the local site to manage its own changes and to incorporate the changes of the shared version at periodic intervals. We call this process synchronization. We survey current approaches that address problems of sharing and local modification, and we present the CONCORDIA model, which supports carefully controlled divergence of a local version from a shared terminology. CONCORDIA provides the underlying design and methodology for the implementation of a synchronization-support tool.
Keywords: Controlled Medical Terminology; Terminology Maintenance